INTENTIONAL BODILY HARM. - Ollamurotov Mardon Amir oʻgʻli (TADQIQOTLAR.UZ, 2024)
Annotation. Intentional bodily harm, often driven by various motives and underlying psychological factors, remains a significant societal concern. This article delves into the complexities surrounding intentional harm, examining its prevalence, motives, consequences, and prevention strategies. Through literature analysis and empirical insights, we aim to provide a comprehensive understanding of this multifaceted issue and offer recommendations for intervention and mitigation.